BTG2-deficient mast cells remodel the tumor and tumor-draining lymph node microenvironment leading to chemotherapy resistance in breast cancer - Zhang, Xiaoqian; Wang, Jiayi; Liu, Ziyu; Wen, Jiahuai; Kang, Mengling; Fang, Chen; Ren, Liping (Frontiers in Immunology, 2025)
BackgroundBreast cancer is currently the most frequently diagnosed malignancy worldwide, with chemotherapy resistance being a major contributor to breast cancer-related mortality and distant metastasis. The role of lymph nodes as the initial site of immune defense remains controversial, particularly regarding whether complete dissection or preservation is necessary during breast cancer surgery.MethodsWe performed single-cell RNA sequencing (scRNA-seq) on cells derived from metastatic tumor draining lymph nodes and tumor tissue of four breast cancer patients exhibiting either sensitivity or resistance to neoadjuvant chemotherapy (NAC).ResultsMast cells with low BTG2 expression were identified in the metastatic lymph nodes and in situ tumor of the NAC-resistant group. Mast cells with low BTG2 expression have enhanced migratory capacity and are preferentially recruited to lymph nodes by cytokines such as CCL5, secreted by tumor cells during metastasis. Mechanistically, the mast cells with low BTG2 suppress anti-tumor immunity by inducing Treg cell production through IL-2 secretion, particularly within tumor-draining lymph nodes. Furthermore, the mast cells with low BTG2 promote NAC resistance by inducing fibroblast precursor cells to differentiate into α-SMA-positive fibroblasts via the Tryptase-PAR-2-pERK signaling pathway, leading to excessive collagen fiber production. Finally, we demonstrated that combining radiotherapy upregulating the expression of BTG2 in mast cells with chemotherapy enhances therapeutic efficacy in a murine model.ConclusionsThis study highlights the immunoregulatory role of mast cells in the breast cancer tumor microenvironment and establishes a link between BTG2 expression in mast cells and neoadjuvant chemotherapy response. These findings provide a foundational basis for preserving functional lymph nodes and optimizing combined radiotherapy treatment strategies.